Study on Editing Method to Improve Speech Intelligibility Based on Speech Perception Characteristics of Elderly People - ICHIMANDA, Ayato; KITAOKA, Norihide; NISHIMURA, Ryota; NAGAO, Takumi (Journal of Japan Society for Fuzzy Theory and Intelligent Informatics, 2018)
In a super-aging society in recent years, declining auditory function of elderly people is regarded as a problem. If the hearing function deteriorates, communication with conversation also becomes difficult. The elderly support system using the spoken dialog system has been developed, however the synthesized speech used in such a system is difficult for the elderly to listen. In this study, we conducted listening experiments for elderly people to analyzed the auditory function of elderly people. In the listening experiment, word intelligibility tests were conducted to analyze the discrimination rate for phonemic unit (consonant part, vowel part). As a result, there were many confusion in phoneme perception between fricatives, affricates and plosives. From this result, we applied consonant emphasis processing to speech based on the auditory function of the elderly people, and then we investigated whether the processed speech is easy for the elderly to listen. The consonant emphasis processing was performed on phonemes where there were many confusion in phoneme perception, such as /k/, /s/, /t/, /h/, /ky/, /sy/, /ch/. The processing method is to amplify the amplitude of the consonant part to 400% of the original speech. In the evaluation experiment of processed speech, we conducted listening experiments for the same subjects in the word intelligibility test and compared the correct answer rates. As a result, correct answer rate for processed speech is improved in some phonemes.